Analysis of chosen parts of social insurance in Czech republic and in Slovakia - Korousová, Alice; Maaytová, Alena; Klazar, Stanislav, 1974-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2011)
The work is concerned with retirement and health insurance. The analysis deal with changes made in legislation of social insurance and it proves effects on state budget. The work involves comparison of analyzed results between Czech republic an Slovak republic.
Vedoucí práce: Alena Maaytová
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2011
Rok obhajoby 2011
Keywords: zdanění a daňová politika [obor bakal. práce]; bakalářské práce; bachelor's theses